An Investigation on the Usability of Mobile Travel Guide Application: A Comparison Study - Angeline, Lee; Siti Shukhaila, Shaharuddin; Ng, Edmund Giap Weng; Syaryfah Fazidawaty, Wan Busrah (American Scientific Publishers, 2018)
The sophistication of interactive travel guide mobile application technologies has increased rapidly over the years. A dynamic travel app-user interaction during traveling is an important part of user experience (UX). However, in regular travel application settings, essential user interface (UI) design for easy navigation can be a challenged for some user. In this paper, a study of three different travel guide applications available on the market was carefully chosen to further experiment and measure the user experience through System Usability Scale (SUS). The method of 1-Way Within Subjects ANOVA (or repeated measure design) was conducted to determine the significant differences between the three travel guide applications design on a sample size of 30 participants. Findings show that there was a significant effect of travel guide type, with reading of Wilks’ Lambda = 0.35, F(2,28) = 25.23, p = 0.00. Hence, Paired Samples T -Tests were conducted to compare the three post hoc tests. Results indicated that interface design type does have an effect on user experience. Consequently, the application with the most familiar function and the simplest, straight forward visual display were thought to be the most effective, efficient, and satisfied from participants.